Clonal hematopoiesis associates with prevalent and incident cardiometabolic disease in a cardiac catheterization cohort - Jessica A. Regan; Lydia Coulter Kwee; Navid A. Nafissi; Alexander G. Bick; William E. Kraus; Pradeep Natarajan; Siddhartha Jaiswal; Svati H. Shah (PLoS ONE, 2026)
Background Clonal hematopoiesis of indeterminate potential (CHIP) is the age-related presence of expanded somatic clones secondary to leukemogenic driver mutations and is associated with cardiovascular (CV) disease and mortality. We sought to evaluate relationships between CHIP with cardiometabolic diseases and incident outcomes in high-risk individuals. Methods CHIP genotyping was performed in 8469 individuals referred for cardiac catheterization at Duke University (CATHGEN study) to identify variants present at a variant allele fraction (VAF) ≥2%. Associations were tested among any CHIP variant, large CHIP clones (VAF > 10%) and individual CHIP genes with prevalent cardiometabolic traits. Cox proportional hazard models tested CHIP associations with time-to-overall mortality and Fine-Gray analyses tested CHIP associations with incident cardiovascular outcomes. Results We identified 463 CHIP variants in 427 individuals (5.0%) of which 268 (3.2%) harbored large CHIP clones. CHIP and large CHIP were associated with lower odds of obesity (OR 0.79 [95% CI 0.65–0.98], p = 0.03; OR 0.76 [95% CI 0.57–0.99], p = 0.04, respectively). CHIP was associated with prevalent heart failure (HF, OR 1.25 [95% CI 1.01–1.55], p = 0.04; especially for non- DNMT3A CHIP (OR 1.38 [95% CI 1.04–1.82], p = 0.02). CHIP was also associated with incident events: Non- DNMT3A CHIP was associated with increased risk of time-to-HF hospitalization (HR 1.29 [95% CI 1.02–1.63], p = 0.03). Conclusions In high-risk individuals referred for cardiac catheterization, large CHIP and non- DNTM3A CHIP were associated with obesity, prevalent HF, incident CV events. These findings strengthen the importance of CHIP as a biomarker for CV disease and highlight the contributing risk of large CHIP clones and non- DNMT3A CHIP variants.